A multicenter, open‐label phase II study of recombinant CPT (Circularly Permuted TRAIL) plus thalidomide in patients with relapsed and refractory multiple myeloma. Issue 11 (29th September 2014) - Geng, Chuanying; Hou, Jian; Zhao, Yaozhong; Ke, Xiaoyan; Wang, Zhao; Qiu, Lugui; Xi, Hao; Wang, Fuxu; Wei, Na; Liu, Yan; Yang, Shifang; Wei, Peng; et al.
<x xml:space="preserve">Abstract</x> Circularly permuted TRAIL (CPT), a recombinant mutant of human Apo2L/TRAIL, is a novel antitumor candidate for multiple myeloma (MM) and other hematologic malignancies. In this phase II study, the safety and efficacy of CPT plus thalidomide was investigated in thalidomide‐resistant MM patients. A total of 43 patients were recruited into three CPT plus thalidomide cohorts based on CPT dosage in sequence: 5 mg/kg (n = 11), 8 mg/kg (n = 17), and 10 mg/kg (n = 15). CPT was administered via intravenous infusion on days 1–5, and thalidomide was given orally at 100 mg once daily in each 21‐day cycle. The overall response rate (ORR) of 41 efficacy‐evaluable patients was 22.0% (2 complete response, 3 near complete response, and 4 partial response). No significant difference in the ORR was observed among the three dose cohorts; however, the ORR tended to be higher with the higher‐dose regimen. Median progression‐free survival and median duration of response were 6.6 months and 6.1 months, respectively. The most common treatment‐related adverse events (TRAEs) were neutropenia (46.5%), leukopenia (41.9%), fever (37.2%), elevated AST (32.6%), and elevated ALT (20.9%). TRAEs of Grade 3–4 were mainly neutropenia (18.6%), anemia (9.3%), elevated AST (7.0%), and leukopenia (4.7%). No significant differences were found in the incidence and severity of TRAEs among the three cohorts. In conclusion, CPT plus thalidomide was well tolerated with no occurrence of dose‐limiting toxicities and demonstrated promising antitumor activity in RRMM patients. CPT at 10 mg/kg for 5 days in combination with thalidomide and dexamethason will be studied in the next clinical trial. Am. J. Hematol. 89:1037–1042, 2014. © 2014 Wiley Periodicals, Inc.